Analyzing the Trade-Offs of Data Sharing in Social Networks and Privacy Concerns - Muhammad Shairoze Malik (International Journal for Electronic Crime Investigation, 2024)
On social media sites, disclosing personal information can result in advantages like tailored experiences and targeted advertisements, but it can also carry concerns like privacy violations. The trade-offs between these advantages and hazards are examined in this analysis. The importance of addressing issues with data ethics, security, prejudice, and reputation is emphasized. The prominent Cambridge Analytica scandal underscores the risks of improper data handling. Governments have responded with privacy legislation, but there are still issues juggling regulation and scientific advancement. Users carefully weigh the threats to their privacy with the rewards. Benefits include personalized advice and information from research. To counter breaches and exploitation of secrecy, however, ethical frameworks are required. Overregulation impedes research is one issue. Overall, it’s crucial to strike a balance between the risks of privacy loss and the benefits of tailored experiences and targeted marketing from shared data. This trade-off analysis seeks to comprehend the intricate dynamics of privacy in the digital age.